Daclizumab reduces CD25 levels on T cells through monocyte-mediated trogocytosis. (February 2014) - Zhang, Y; McClellan, M; Efros, L; Shi, D; Bielekova, B; Tang, MT; Vexler, V; Sheridan, JP
Daclizumab is a humanized monoclonal antibody that prevents interleukin-2 (IL-2) binding to CD25, blocking IL-2 signaling by cells that require high-affinity IL-2 receptors to mediate IL-2 signaling. The phase 2a CHOICE study evaluating daclizumab as a treatment for multiple sclerosis (MS) included longitudinal analysis of activated T cell counts. Whereas an exposure-dependent relationship was observed between daclizumab and reductions in HLA-DR + -activated T cells, a similar relationship was not observed for reductions in CD25 levels. The objective of this report is to determine the mechanism by which daclizumab reduces CD25 levels on peripheral blood mononuclear cells (PBMCs) using cytometric techniques. Daclizumab reduced T cell CD25 levels through a mechanism that required the daclizumab-Fc domain interaction with Fc receptors (FcR) on monocytes, but not on natural killer (NK) cells, and was unrelated to internalization or cell killing. Activated CD4 + T cells and FoxP3 + Treg cells showed evidence of trogocytosis of the CD25 antigen in the presence of monocytes. A daclizumab variant that retained affinity for CD25 but lacked FcR binding did not induce trogocytosis and was significantly less potent as an inhibitor of IL-2-induced proliferation of PBMCs. In conclusion, Daclizumab-induced monocyte-mediated trogocytosis of CD25 from T cells appears to be an additional mechanism contributing to daclizumab inhibition of IL-2 signaling.